Anti-TLR4 biological response to titanium nitride-coated dental implants: anti-inflammatory response and extracellular matrix synthesis - Oliva, Stefano; Diomede, Francesca; Della Rocca, Ylenia; Mazzone, Antonella; Marconi, Guya Diletta; Pizzicannella, Jacopo; Trubiani, Oriana; Murmura, Giovanna (Frontiers in Bioengineering and Biotechnology, 2023)
Osteointegration is a key process during dental implant placement and it is related to titanium surface topography. Implant coating and surface modification methods are able to ameliorate the bone production and the osteogenic process. The current work aimed at evaluating the biological outcomes of two different surface of dental implants, machined and Titanium Nitride (TiN) coated, at inflammation level using an in vitro model of human periodontal ligament stem cells (hPDLSCs). The TLR4/MyD88/NFκB p65/NLRP3 pathway induced by the P. Gingivalis lipopolysaccharide (LPS-G) was studied by means of gene and protein level expression. Moreover, expression of Vimentin, Vinculin and Fibronectin was evaluated to investigate the effects on the cells adhesion and extracellular matrix (ECM) deposition. The results of the present study suggest that TiN coated titanium disks may modulate the inflammation by the suppression of TLR4/MyD88/NFκB p65/NLRP3 pathway and accelerate ECM apposition.